A equivalência de estímulos como modelo do significado - de Rose, Julio C.; Bortoloti, Renato (Acta Comportamentalia, 2009)
<!--[if gte mso 9]> Normal 0 21 false false false ES-MX X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" Priority="61" SemiHidden="false" UnhideWhenUsed="false" Name="Light List Acce